PERAN JOB SATISFACTION DALAM MEMEDIASI PENGARUH JOB-LEISURE CONFLICT TERHADAP TURNOVER INTENTION - Narita Adenda Telu Widya; Insan Ratigan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This study aims to determine the influence of Job-Leisure Conflict on Turnover Intention with Job Satisfaction as Mediator at PT Hanindo Express Utama. The population of the study is 58 employees with 51 employee’s sample. The analytical method used is The Simple Mediation Model. From this research Job Satisfaction mediate the influence of Job Leisure Conflict on Turnover Intention. Job-Leisure Conflict cannot directly influence Turnover Intention.